El Brexit y su impacto en la Europa de los derechos: el desafío británico al Derecho constitucional europeo - Tomás Mallén, Beatriz (Revista de Derecho Político, 2017)
Resumen: El presente artículo examina críticamente la decisión histórica de retirada de la UE adoptada en el Reino Unido en el referéndum del Brexit de 23 de junio de 2016, desde una perspectiva de Derecho Constitucional Europeo. En efecto, se hace hincapié en el impacto negativo del Brexit en la construcción de una Europa de los derechos humanos. Desde este punto de vista, se destaca la permanente actitud vacilante del Reino Unido entre el reclamo de la supremacía británica y la necesidad de fortalecer una cultura constitucional europea común, teniendo en cuenta las dinámicas de la «adhesión» y de la «exclusión parcial» tanto en relación con la UE como con el Consejo de Europa y sus principales instrumentos de derechos humanos. Por otra parte, el artículo somete a análisis las inconsistencias del «Libro Blanco del Brexit» presentado como documento oficial del Gobierno británico en el campo de los derechos fundamentales. En fin, se concluye que el Brexit puede ser una decisión histórica equivocada que debilita la cultura constitucional británica y, correlativamente, una oportunidad para que los demás Estados miembros de la UE optimicen el proceso de integración europea y la calidad de sus propios regímenes democráticos. Summary: I. Introduction: the Brexit as a result of the eurosceptic british constitutionalism. II. The United Kingdom as a promoter (paradoxically) of a comprehensive Europe of rights. 1. The emblematic constitution in London of the Council of Europe. 2. The late assumption of the basic standards of European rights culture. III. The initial exclusion and successive british exceptions to the european rights community. 1. The EFTA and the promotion of the integrated Europe of rights, without integrating it. 2. Partial exceptions on rights in the revisions of the European Treaties. 3. The total amendment to the Europe of rights: rejection of the Charter of Fundamental Rights of the European Union. IV. The Brexit road map as an abandonment of the European constitutional order of rights. 1. Distancing from the European catalog of rights. 2. Disregard for the CJEU. 3. The road map at the crossroads: the thin frontier between the European Union and the Council of Europe. V. Final thoughts: the commitment to the strengthening of a Europe of rights, despite Brexit. Abstract: This essay critically examines the historical decision of withdrawal from the EU adopted in United Kingdom in the Brexit referendum of 23 June 2016 under a European Constitutional Law perspective. Indeed, the focus is put on the negative impact of the Brexit in building a Europe of human rights. From this point of view, the author highlights the United Kingdom’s permanent hesitation between a claim for the British supremacy and a need for strengthening a Common European Constitutional culture, by taking into account the dynamics of either «accession» or «partial out-puts» in relation to both the EU and the Council of Europe and their main human rights instruments. On the other hand, the paper submits to scrutiny the inconsistencies of the British Government’s official «Brexit White Paper» in the field of fundamental rights. The author concludes that the Brexit might be a wrong historic decision weakening the British Constitutional culture and, correlatively, an opportunity for the other EU Member States to optimize the European integration process as well as the quality of their own democratic regimes.